Using Acoustic Emission to Evaluate Fracture Toughness Energy Release Rate (GI) at Mode I Delamination of Composite Materials - Oskouei, Amir Refahi; Zucchelli, Andrea; Ahmadi, Mehdi; Minak, Giangiacomo (IntechOpen, 2012)
None